Pengaruh Social Media Marketing Terhadap Keputusan Pembelian yang Dimediasi Word of Mouth Marketing - Hazler Hermawan Hasan; Komang Agus Satria Pramudana (Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to analyze the influence of Social Media Marketing mediated by word of mouth on purchasing decisions at the JajanDaging Online Store. Many companies are switching from conventional promotional media to digital promotional media in marketing their products, because most Indonesian people already have internet access. Social media is one of the media that can be used to carry out promotional activities using the internet. The use of Instagram social media will form an effective marketing communication strategy, namely word of mouth. This research is a quantitative research using non-probability sampling techniques using questionnaires to collect data. The number of samples taken was 114 respondents, the JajanDaging consumers in the cities of Jakarta, Bogor, Depok, Tangerang and Bekasi. The analysis technique used is the Sobel test using path analysis and the VAF test. Based on the results of the analysis it was found that social media marketing variables had a positive and significant effect on purchasing decisions for JajanDaging consumers, social media marketing variables had a positive and significant effect on word of mouth for JajanDaging consumers, word of mouth variables had a positive and significant effect on purchasing decisions for JajanDaging consumers , and the word of mouth variable significantly mediates the relationship between social media marketing and purchasing decisions for JajanDaging consumers.